EFFICIENCY EVALUATION THE CLIENT POLICY OF COMMERCIAL BANK - Yury Metel; Natalia Kunitsyna (Вестник Северо-Кавказского федерального университета, 2022)
The essence and content of client policy of commercial bank are considered. The different directions of customer relations allowing to evaluate efficiency of client policy of credit institution and also their interference are provided and characterized. The overview of techniques of an efficiency evaluation of client policy is carried out, their benefits and shortcomings are allocated.